A review of nuclear fuel performance codes - Aybar, HS; Ortego, P (Pergamon-Elsevier Science Ltd, 2005)
The reliable prediction of nuclear fuel rod behaviour of nuclear power reactors constitutes a basic demand for safety-based calculations, for design purposes and for fuel performance assessments. There are many nuclear fuel performance codes, some of which are available in public domain. The recent fuel design and improvement activities are focused on to extend the burnup, of fuel, and the use of new materials. Thus, the most important limitation of codes is the burnup, validity limit. In this study, a review of the analytical capability of some of the existing computer codes for nuclear fuel performance calculations to highlight major strengths and weaknesses is performed. (C) 2005 Elsevier Ltd All rights reserved.
Keywords: nuclear fuel; fuel performance